Unlocking Potential: Investigating the Impact of Education among Rural Women Agricultural Workers of Puducherry - YASAM, LAKSHMI NARAYANA REDDY; RAJENDIRAN R; C N ANSHIDA BEEVI (Journal of Extension Education, 2023)
Education is a powerful tool that improves socio-economic conditions and empowers individuals, especially women. However, women face gender disparities resulting in lower literacy rates compared to men. Besides understanding the educational status of women agricultural workers and their accessibility to schools and colleges, this study investigated the impact of education on their income levels, language proficiency in mother tongue and English and their preferences to spend more on their children education. Using a mixed-methods approach, data were collected and analysed from a random sample of 5,044 rural women agricultural workers across 98 revenue villages in the Union Territory of Puducherry. The findings revealed that half of the respondents completed education ranging from 6th to 10th class, where as one out of every four respondents were illiterates and a small percentage possessed higher qualifications of a degree and above. Most of the respondents had access school and six out of ten had access to college within 5 km range. The study established a positive correlation between education level and both individual and family income and a higher level of language proficiency in both the mother tongue and English. The educated rural women workers showed a preference for private schools to educate their children, indicating a growing inclination to spend more on education.